Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1996
DOI: 10.1063/1.471317
|View full text |Cite
|
Sign up to set email alerts
|

Diffusive dynamics of the reaction coordinate for protein folding funnels

Abstract: The quantitative description of model protein folding kinetics using a diffusive collective reaction coordinate is examined. Direct folding kinetics, diffusional coefficients and free energy profiles are determined from Monte Carlo simulations of a 27-mer, 3 letter code lattice model, which corresponds roughly to a small helical protein. Analytic folding calculations, using simple diffusive rate theory, agree extremely well with the full simulation results. Folding in this system is best seen as a diffusive, f… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

25
525
3
4

Year Published

1997
1997
2008
2008

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 480 publications
(557 citation statements)
references
References 24 publications
25
525
3
4
Order By: Relevance
“…Therefore, the apparent success of two-state analyses already suggests that even one-dimensional projections may suffice to describe coarse folding properties. The first direct evidence supporting the validity of one-dimensional folding surfaces has come from the analysis of simulations in the cubic lattice (28). Further support comes from the reasonable success in calculating relative folding rates from protein structures using one-dimensional free energy surfaces (29).…”
Section: Free Energy Projections and Reaction Coordinatesmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, the apparent success of two-state analyses already suggests that even one-dimensional projections may suffice to describe coarse folding properties. The first direct evidence supporting the validity of one-dimensional folding surfaces has come from the analysis of simulations in the cubic lattice (28). Further support comes from the reasonable success in calculating relative folding rates from protein structures using one-dimensional free energy surfaces (29).…”
Section: Free Energy Projections and Reaction Coordinatesmentioning
confidence: 99%
“…more compact)(3). Effective diffusion coefficients for folding on a one-dimensional energy surface are therefore expected to be complex functions of the order parameter, including both dynamic and energetic terms (28).…”
Section: Free Energy Projections and Reaction Coordinatesmentioning
confidence: 99%
“…The motion of this coordinate for small lattice models is diffusive, and rates are predicted well using a diffusional rate theory (25), since the free energy barrier is broad. It has also been shown that at the folding midpoint of the lattice protein the effects of site mutations faithfully reflect the structural correlations in the ensemble at the top of the barrier (11).…”
Section: The Funnel Picture and Folding Reaction Coordinatesmentioning
confidence: 99%
“…Since tertiary contacts are a dominant source of protein stabilization, a collective coordinate measuring the fraction of such contacts which are correct, Q, has been used in a number of off-lattice and lattice simulations (22)(23)(24)(25). The motion of this coordinate for small lattice models is diffusive, and rates are predicted well using a diffusional rate theory (25), since the free energy barrier is broad.…”
Section: The Funnel Picture and Folding Reaction Coordinatesmentioning
confidence: 99%
“…Theoretical studies based on simulations of the reaction rate for complex systems, such as peptides and proteins, often show simple exponential kinetics (11)(12)(13). To be able to determine both the preexponential factor and the free energy barrier from simulations, it is necessary to have a method of constructing the onedimensional projected FES in terms of an appropriate reaction coordinate, if such exists.…”
mentioning
confidence: 99%